Proliferation issues related to fast SMRs. (November 2015) - Frieß, Friederike; Kütt, Moritz; Englert, Matthias
Highlights: A long lived core SMR design is modeled for depletion calculations. Depletion calculations are carried out to assess proliferation potential. At EOL, the plutonium inventory is determined to be 160 kg. Assessment shows separated fissile material to be highly attractive for weapons. Dose rates of spent fuel assemblies are below 5 Sv/h. Abstract: This paper contributes to the literature on proliferation risks of small modular reactors. After a general discussion of SMR developments, in the main section of this paper we present an analysis of a generic sodium-cooled fast reactor designed to sustain an unusual lifetime of 30 years, similar to concepts such as the Toshiba 4S. For this reactor, material composition over lifetime is calculated and its material attractiveness compared to (spent) fuel from other reactor types. Depletion calculations show that a significant amount of plutonium is produced over time with an isotopic composition highly attractive for military purposes.